Indicadores de control de calidad como requisitos para la acreditación de Laboratorios Clínicos - Curillo Llanganate, Nancy Beatriz (2022)
ABSTRACT: The objective of this bibliographic review project was to identify the quality control indicators that are required for the accreditation of Clinical Laboratories, through a documentary review of existing publications. The type of research is descriptive and non-experimental design, since, to carry out this project, information was collected from the literature published in recognized scientific databases such as Google Scholar, Ebook Central, Scielo, Scopus, Dspace, Redalyc. Scientific articles or books published since 2011 were included. Information was collected on the ISO 15189 standard, which is an accreditation standard for laboratories and requires compliance with some management requirements and technical requirements with qualified personnel to guarantee quality. of laboratory processes. The identification of indicators within the preanalytical area is considered the most important, some examples of quality indicators in the preanalytical area are: number of samples with incorrect identification, number of rejected samples, number of insufficient samples, number of lost samples, Excessive number of venipuncture. Of the indicators mentioned, the most frequent is the number of samples with incorrect identification, which corresponds to 6 articles, that is, several authors describe the same indicator in the pre-analytical phase and it is the one that is most frequently found. For laboratory accreditation, qualified professional competence and duly calibrated equipment must be available to obtain technically valid and comparable results among other laboratories worldwide.